Fabrication of Ag/Al(OH)(3) mesoporous nanocomposite film - Seo, Young Ik; Lee, Young Jung; Kim, Dae-Gun; Lee, Kyu Hwan; Do Kim, Young (ELSEVIER SCIENCE BV, 2011)
In this study, a Ag/Al(OH)(3) mesoporous nanocomposite film was fabricated for antibacterial and biomedical applications. First, a mesoporous Al(OH)(3) layer was prepared by alkali surface modification of an Al substrate. The prepared Al(OH)(3) layer was composed of flaky crystals woven within and covering the entire substrate surface so that the specific surface area was considerably enlarged because of voids of several tens of nanometers between the flakes. The substrate covered by the Al(OH)(3) layer was immersed in a solution of ethylene glycol where polyvinylpyrrolidone (PVP) and silver nitrate (AgNO3) were dissolved for the polyol process. When the solution with the substrate was heated to 120 degrees C and maintained at that temperature up for 4 h, the Ag nanoparticles were nucleated and grown at the mesoporous Al(OH)(3) layer surface, as well as in the solution as colloids. It is believed that the Al(OH)(3) layer is a suitable matrix for the fabrication of mesoporous nanocomposite film. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: SHAPE-CONTROLLED SYNTHESIS; SILICA THIN-FILMS; SILVER NANOPARTICLES; CARBON NANOTUBES; POLYOL PROCESS; SURFACE; LAYER; GOLD